Economic impact of psychiatric relapse and recidivism among adults with schizophrenia recently released from incarceration: a Markov model analysis. (March 2015) - Lin, Iris; Muser, Erik; Munsell, Michael; Benson, Carmela; Menzin, Joseph
Abstract Objectives: To develop an economic model that estimates the cost burden of psychiatric relapse and recidivism among patients with schizophrenia recently released from incarceration from a US state government perspective. Methods: A Markov state-transition model was developed to estimate the numbers of schizophrenia patients recently-released from incarceration who would experience psychiatric relapse and/or arrest and re-incarceration over a period of 3 years, along with corresponding costs. The model includes three health states: (1) in community, on therapy, (2) in community, off therapy, and (3) incarcerated. It is assumed that a patient's probability of psychiatric hospitalization increases with treatment discontinuation, and the probability of arrest increases with the occurrence of a prior psychiatric hospitalization. Data from the US Census and Bureau of Justice Statistics were used to estimate the model population. Published literature was used to estimate the risks of psychiatric relapse, arrest, and all cost inputs. State-specific incarceration rates and sentence length data (from the state of Florida) were applied. The impact on outcomes and costs was evaluated by varying the rates of anti-psychotic treatment following release from incarceration and the annual risk of medication discontinuation. Results: Among 34, 500 persons released from incarceration in the state of Florida annually, 5307 were estimated to have schizophrenia. The cumulative 3-year costs to the state government were 21, 146, 000 and 25, 616, 000 for criminal justice and psychiatric hospitalization costs, respectively (3984 per patient criminal justice; 4827 per patient hospitalization costs). A relative 20% increase in the proportion of patients receiving antipsychotic treatment following release from incarceration decreased total cumulative costs over 3 years by 1, 871, 100 (353 per patient). Conclusions: The economic impact of psychiatric relapse and recidivism among patients with schizophrenia is substantial from the state government perspective. This general model can be made state-specific by utilizing local criminal justice data sources.